2006
DOI: 10.4103/0028-3886.27160
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto′s encephalopathy and motor neuron disease: A common autoimmune pathogenesis?

Abstract: Hashimoto's encephalopathy is a rare complication of autoimmune thyroiditis not associated with thyroidal function decline. We report a 50-year-old man presenting with lower motor neuron symptoms evolving over 3 years and changes in behavior associated with attentive and cognitive impairment occurring in the last few months. Memory deficits, emotional instability, marked dysarthria, mild symmetric weakness of the lower extremities and fasciculations were the most striking clinical features. EEG was diffusely s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The other was a 50-year-old man presenting with lower motor neuron symptoms that had evolved over three years, and changes in behavior associated with attentive and cognitive impairment. This patient’s cranial MRI also revealed multiple subcortical white matter lesions [37].…”
Section: Discussionmentioning
confidence: 66%
“…The other was a 50-year-old man presenting with lower motor neuron symptoms that had evolved over three years, and changes in behavior associated with attentive and cognitive impairment. This patient’s cranial MRI also revealed multiple subcortical white matter lesions [37].…”
Section: Discussionmentioning
confidence: 66%
“…The fact that autoimmune encephalitis can develop in cases with Hashimoto thyroiditis in the presence of normal thyroid hormone levels and elevated antithyroid peroxidase autoantibodies suggest that parts of the brain related to the autonomic nervous system can be affected (Castillo et al 2006). Besides, Harzheim et al (2006) have reported a case of Hashimoto thyroiditis with motor neuron disease accompanying encephalitis, suggesting a common autoimmune pathogenesis. Disturbed HRV in eHT might be a consequence of involvement of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients have HE and other immune diseases. A possible common autoimmune pathogenesis was supposed in a 50-year-old man with HE and motor neuron disease (Harzheim et al, 2006). He presented with chronic progressive lower motor neuron symptoms (paraparesis and fasciculations in all extremities) and encephalopathy characterized by memory and attention deficits, emotional instability, aggressiveness, and dysarthria.…”
Section: Peripheral Nervous System Involvementmentioning
confidence: 99%